Cutaneous manifestations in patients with chronic kidney diseases on haemodialysis - Baghel, Nekram; Awasthi, Sankalp; Kumar, Sweta S. (International Journal of Research in Medical Sciences, 2017)
Background: Cutaneous and mucosal disorders are of the common problems in patients on long term haemodialysis. The aim of this study was to evaluate the frequency and nature of cutaneous lesions among patients with chronic kidney diseases who received maintenance haemodialysis. Methods: Eighty patients with chronic kidney diseases on haemodialysis were studied. All of the patients were fully examined for cutaneous, hair, nail and mucosal changes. Diagnostic measures such as scraping and biopsy of the lesions was carried out, where necessary. Results: The patients were 30 females and 50 males with a mean age of 47.6 years. The duration of haemodialysis was 36±11 months. All patients included in this study had at least one cutaneous manifestation attributable to CRF. The most prevalent findings were xerosis (66.2%) followed by pallor (57.5%), pruritus (51.25%), infections (33.75%), AV shunt dermatitis (16.25%), pigmentary changes (13.75%), purpura, ecchymoses (8.75%) and perforating disorders (2.5%). Hair changes were diffuse alopecia (16.25%), brittles, lustreless hair (3.75%) and sparse body hairs (1.25%). Oral changes were candidiasis (10%), angular cheilitis (3.75%), gingivitis (2.75%), fissured tongue (2.75%) and lichen planus (1.25%). Nail changes were leukonychia (10%), dystrophic nails (7.5%) onychomycosis (6.25%), subungual hyperkeratosis (5%) and half and half nails (1.25%). Conclusions: At least one cutaneous manifestation is found in all CRF patients. The etiology of CRF does not affect the cutaneous, hair or nail abnormalities. Factors such as diagnostic climate and early treatment influence some disorders such as xerosis, pruritus and infections.